Dielectric Barrier Discharge Ionization in Characterization of Organic Compounds Separated on Thin-Layer Chromatography Plates - Cegłowski, Michał (Public Library of Science, 2014)
A new method for on-spot detection and characterization of organic compounds resolved on thin layer chromatography (TLC) plates has been proposed. This method combines TLC with dielectric barrier discharge ionization (DBDI), which produces stable low-temperature plasma. At first, the compounds were separated on TLC plates and then their mass spectra were directly obtained with no additional sample preparation. To obtain good quality spectra the center of a particular TLC spot was heated from the bottom to increase volatility of the compound. MS/MS analyses were also performed to additionally characterize all analytes. The detection limit of proposed method was estimated to be 100 ng/spot of compound.